2011
DOI: 10.1158/1078-0432.ccr-11-1870
|View full text |Cite
|
Sign up to set email alerts
|

Novel Chromosomal Rearrangements and Break Points at the t(6;9) in Salivary Adenoid Cystic Carcinoma: Association with MYBNFIB Chimeric Fusion, MYB Expression, and Clinical Outcome

Abstract: Objective To investigate the molecular-genetic heterogeneity associated with the t(6:9) in adenoid cystic carcinoma (ACC) and correlate the findings with patient clinical outcome. Experimental Design Multi-molecular and genetic techniques complemented with massive pair-ended sequencing and SNP array analyses were used on tumor specimens from 30 new and 52 previously RT-PCR analyzed fusion transcript negative ACCs. MYB mRNA expression level was determined by quantitative RT-PCR. The results of 102 tumors (30 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
148
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(162 citation statements)
references
References 45 publications
11
148
2
1
Order By: Relevance
“…MYB-NFIB fusion status was investigated using a combination of fusion transcript sequencing, qRT-PCR, FISH, and 3′ rapid amplification of cDNA ends (3′ RACE), as described previously (25). The particular data supporting a scoring of MYB activation in any given sample are given in Supplemental Detection of copy number variation.…”
Section: Methodsmentioning
confidence: 99%
“…MYB-NFIB fusion status was investigated using a combination of fusion transcript sequencing, qRT-PCR, FISH, and 3′ rapid amplification of cDNA ends (3′ RACE), as described previously (25). The particular data supporting a scoring of MYB activation in any given sample are given in Supplemental Detection of copy number variation.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed genomic characterization (including next generation sequencing) of several such cases have revealed insertions of a segment from 9p23-p22.3, including the 3 0 -part of NFIB, immediately centromeric to the MYB locus ( Fig. 3) [9,20,21]. In these cases we can only speculate that enhancer elements upstream of MYB perhaps in combination with other regulatory elements in the 3 0 -part of NFIB and its flanking sequences may contribute to the activation of MYB.…”
Section: Myb-nfib Gene Fusion In Adenoid Cystic Carcinomamentioning
confidence: 98%
“…Though there is some disagreement in the literature regarding the percent of ACC tumors harboring this molecular alteration, most subsequent studies have shown that the majority of ACC have a disrupted MYB gene and/ or evidence of a MYB-NFIB fusion RNA transcript [32][33][34][35][36]. One of the largest independent cohorts separate from the Stenman group came from a study at Stanford University, where 37 cases of ACC were studied by fluorescence in situ hybridization (FISH) of the MYB and NFIB loci, with 65 % of cases showing abnormalities of these loci [34].…”
Section: Introductionmentioning
confidence: 99%